Genomic analysis of Mycobacterium tuberculosis variant bovis strains isolated from bovine in the state of Mato Grosso, Brazil - Anjos, Taís Ramalho dos; Castro, Vinícius Silva; Machado Filho, Edson Silva; Suffys, Philip Noel; Gomes, Harrison Magdinier; Duarte, Rafael Silva; Figueiredo, Eduardo Eustáquio de Souza; Carvalho, Ricardo César Tavares (Frontiers in Veterinary Science, 2022)
The species Mycobacterium tuberculosis variant bovis (M. tuberculosis var. bovis) is associated with tuberculosis, mainly in cattle and buffaloes. This pathogen has the potential to infect other mammals, including humans. Tuberculosis caused by M. tuberculosis var. bovis is a zoonosis clinically identical to tuberculosis caused by Mycobacterium tuberculosis, and the recommended treatment in humans results in the use of antibiotics. In this study, we used the whole genome sequencing (WGS) methodology Illumina NovaSeq 6000 System platform to characterize the genome of M. tuberculosis var. bovis in cattle circulating in Mato Grosso, identify mutations related to drug resistance genes, compare with other strains of M. tuberculosis var. bovis brazilian and assess potential drug resistance. Four isolates of M. tuberculosis var. bovis of cattle origin representing the main livestock circuits, which had been more prevalent in previous studies in the state of Mato Grosso, were selected for the genomic study. The genome sizes of the sequenced strains ranged from 4,306,423 to 4,332,964 bp, and the GC content was 65.6%. The four strains from Mato Grosso presented resistance genes to pncA (pyrazinamide), characterized as drug-resistant strains. In addition to verifying several point mutations in the pncA, rpsA, rpsL, gid, rpoB, katG, gyrB, gyrA, tlyA, embA, embB, embC, fgd, fbiB and fbiC genes, these genes were similar to antibiotic resistance in more than 92% of the Brazilian strains. Therefore, our results indicated a high genetic diversity between our isolates and other M. tuberculosis var. bovis isolated in Brazil. Thus, multiple transmission routes of this pathogen may be present in the production chain. So, to achieve a bovine tuberculosis-free health status, the use of the WGS as a control and monitoring tool will be crucial to determine these transmission routes.